PERENCANAAN PENINGKATAN JALAN PADA RUAS JALAN PACITAN-NGADIROJO - Bakhtiar Andhi Harsono; Sigit Winarto; Yosef Cahyo Setianto (Faculty of Engineering, Kadiri University, 2018)
The Pacitan-Ngadirojo road section is one of the East Java Province Roads located in Pacitan District, which includes cross-district roads. The condition of the Pacitan-Ngadirojo road segment is generally a flat road that has several bends, inclines and derivatives along the link. Passing through a number of subdistricts and villages in the Pacitan Regency area which has right and left sides, there are settlements, agricultural land, plantations, gardens, rice fields, and traditional shopping places.To analyze road performance, the writer uses the method Manual Kapasitas Jalan Indonesia (MKJI, 1997), while to calculate the thickness of road pavement, we use the method Bina Marga (1987).From the results of the road performance analysis, data were obtained as follows: Degree of Saturation (DS) on the PacitanNgadirojo road segment beginning in 2011 amounted to 0.047 while the performance analysis for the next 10 years obtained a DS of 0,078. This means that the level of road services on the road segment has not yet taken into account traffic actions or management, which in this case is road widening.For the calculation of pavement thickness with the Bina Marga Method the flexible pavement thickness on the PacitanNgadirojo road section is 7,5 cm. Ruas jalan Pacitan-Ngadirojo merupakan salah satu Jalan Propinsi Jawa Timur terletak di Kabupaten Pacitan, yang termasuk jalan lintas kecamatan. Kondisi ruas jalan Pacitan-Ngadirojo secara umummerupakan jalan datar yang memiliki beberapa tikungan, tanjakan dan turunan di sepanjang link tersebut. Melewati beberapa kecamatan dan desa di wilayah Kabupaten Pacitan yang sisi kanan dan kiri terdapat pemukiman, lahan pertanian, perkebunan, tegal, sawah, dan tempat perbelanjaan tradisional. Untuk analisa kinerja jalan penulis menggunakan metode Manual Kapasitas Jalan Indonesia (MKJI 1997), sedangkan untuk menghitung tebal perkerasan jalan, kami menggunakan metode Bina Marga (1987). Dari hasil analisa kinerja jalan didapatkan data-data sebagai berikut : derajat kejenuhan (DS) pada ruas jalan Pacitan-Ngadirojo awal tahun 2011 sebesar 0,047 sedangkan analisa kinerja untuk 10 tahun yang akan datang didapatkan DS sebesar 0,078. Hal ini berarti tingkat pelayanan jalan pada ruas jalan tersebut belum memerlukan adanya tindakan atau manajemen lalu lintas, yang dalam hal ini pelebaran jalan.Untuk perhitungan tebal perkerasan dengan Metode Bina Marga tebal perkerasan lentur pada ruas jalan Pacitan-Ngadirojo setebal 7,5 cm.